(untitled) (Fiep Bulletin - online, 2012)
In most fitness gyms, is common sense that the exercise performed at low execution speed induces greater hypertrophic response. The objective of this study was to monitor the behavior of strength, power and right thigh circumference, in individuals beginners to resistance exercise in the weight training room before and after protocol classified as a fast and slow execution speed of movements in concentric-eccentric cycles. The sample consisted of four healthy male volunteers with low levels of strength training. The subjects were divided into two groups, with the first, 2 individuals aged = 26.50±6.36 years old, called the Fast Execution Group (FEG), who performed mechanical actions with a time of 1.5 seconds for each repetition. The second group consisted of 2 individuals aged = 35.00±2.83 years old, called Slow Execution Group (SEG), which held at 6 seconds per repetition. The tests used were: 1RM leg press and leg extension 90° (also used for training), thigh circumference (TC), standing horizontal jump (SHJ), total body mass and height. The tests were performed the day before and 3 days after the intervention. At the end of this study, noted that the training protocol with fast execution speed generated larger responses in tests of percentage falls in the leg press 1RM (0 hours = 10.81%, 6.76% = 24 hours, 48 hours = 2.97% , and 72 hours = 1.35%) in the leg extension chair (0 hours = 24.20%, 16.22% = 24 hours, 48 hours = 20.21% and 14.89% = 72 hours), SHJ (0 hours = 12, 27%, 8.63% = 24 hours, 48 hours = 8.12% and 8.38% = 72 hours) and increase in TC (0 hours = 3.05%, 2.59% = 24 hours, 48 hours = 2.50% , and 72 hours = 2.04). Thus, we can say that in this study, training with FEG generates larger micro muscle damage, thereby increasing the thigh circumference and fall in yield and ultimate strength tests SHJ when compared to the SEG group.